'Holy shame shall warm my heart': Shame and Protestant Emotions in Early Modern Britain. (1st January 2021) - Zhao, Han
ABSTRACT: This article scrutinises shame in early modern Britain through the lens of Protestantism, and explores when, where, and why Protestants felt shame, and how they expressed, interpreted, and utilised this emotion for devotional and moral purposes. It argues that shame was a spiritually-productive and often individual emotion, which was wholeheartedly embraced by Protestants, and constituted an important part of their identity. This article offers a picture which differs from the modern stereotypical assumption that shame is intrinsically a harmful and social emotion, and challenges the view that Christianity had led to the dissolution of a shame culture in Western society.